Bat occurrence and microclimatic conditions of the Sima del Órgano Cave, Mexico - Hernández, Luis; Gómez, Jaime; Reyes, Cyntia (International journal of speleology, 2025)
Caves represent an important type of shelter for many species of bats, particularly in karstic regions. In Mexico, about 60 bat species regularly use caves as roosts. The microclimate of a cave is a key component of the overall cave ecosystem. So, an adequate microclimate can minimize the energetic costs of bats associated with thermoregulation, gestation, embryonic development, parental care, lactation and social interaction. Cave environments are among the least known and most threatened on the planet, which is why we aimed to determine the monthly occurrence of bat species in the Sima del Órgano Cave, estimate the population size of the bat colony and determine the monthly microclimatic conditions of temperature and relative humidity inside the cave. The Sima del Órgano Cave is located in Chiapas, Mexico and is home of five species of mormopid bats (Mormoops megalophylla, Pteronotus fulvus, P. gymnonotus, P. mesoamericanus, and P. psilotis), one natalid (Natalus mexicanus) and a phyllostomid (Leptonycteris yerbabuenae), of these P. gymnonotus and L. yerbabuenae are listed as at risk of extinction in Mexico. Six species are insectivorous, and one is nectarivore; the seven species use caves as main roost and their occurrence is mostly associated to hot caves. The size of the bat colony was of 276,080 (SD ± 1,764) individuals, being P. fulvus and P. psilotis the largest proportion. The Sima del Órgano Cave presented an average annual temperature of 34.1°C and an average relative humidity of 92.6%, corresponding to a hot cave. Based on the number of the occurring species, the population size and the fact that it is home to species at risk of extinction, Sima del Órgano is a priority cave for conservation at a regional level in Mexico.